2009
DOI: 10.2116/analsci.25.1227
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Determination of Trace Amounts of Amantadine Using a Modified Carbon-Paste Electrode

Abstract: A chemically modified carbon-paste electrode has been described for the sensitive and selective determination of amantadine. β-Cyclodextrin was used as modifier. The electrode shows a sub-Nernstian response of 51.0 ± 1.0 mV decade -1 for amantadine in the concentration range of 6.3 × 10 -10 -7.1 × 10 -7 M at 25 C. The optimum pH value was maintained at 4.5 using a 0.02 M acetate buffer. The limit of detection of the electrode was 6.3 × 10 -10 M of amantadine. The electrode responded very rapidly (<60 s) to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To date, the most widely used detection methods for amantadine are chromatographic methods such as LC/GC/HPLC-MS, [83][84][85] near-infrared spectroscopy, 86 piezoelectric immunosensor, 87 and electrochemical techniques, e.g., potentiometry. 88,89 Each of these methods has its strengths, however, all of them are largely constrained by complicating and long-lasting operating procedures and expensive equipment. Our emission-based supramolecular-analytical assay for amantadine in urine and saliva can be readily performed and does not require any sample pre-treatment steps.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most widely used detection methods for amantadine are chromatographic methods such as LC/GC/HPLC-MS, [83][84][85] near-infrared spectroscopy, 86 piezoelectric immunosensor, 87 and electrochemical techniques, e.g., potentiometry. 88,89 Each of these methods has its strengths, however, all of them are largely constrained by complicating and long-lasting operating procedures and expensive equipment. Our emission-based supramolecular-analytical assay for amantadine in urine and saliva can be readily performed and does not require any sample pre-treatment steps.…”
Section: Discussionmentioning
confidence: 99%
“…Binding constants in solution are usually determined from potentiometric titrations or plots of cyclic voltammetry peak potentials vs CD concentration after assessing the guest/host ratio in the complex [33,34]. Potentiometric measurements are more frequently used in studying the inclusion complexes of pharmaceutical compounds with cyclodextrins [35][36][37][38][39][40][41][42][43][44][45][46][47][48], and ion-selective electrodes are employed, for the direct measurement of the guest activity in the solution [49][50][51][52]. Decreased peak currents in cyclic voltammetry and shifts in the oxidation and reduction potentials are observed on complexation, owing to the smaller diffusion coefficients of the complexes than that of the guest alone, and to the relatively high stability of these complexes.…”
Section: Electrochemical Investigations Of the Cd-drugs Interactions mentioning
confidence: 99%
“…This feature shows that cyclodextrin can play a role in sensitivity and selectivity improvement. It is usually used as the host of various guests, such as ferrocene (Fc), 1,2 adamantane, 3,4 and azobenzene 5,6 to form a superamphiphilic complex by geometric compatibility and hydrophobic interactions. 7,8 Li et al 9 reported the reversible control of electron transmission through nanopore-tethered Fc based on the complexation with β-CD.…”
Section: Introductionmentioning
confidence: 99%